2019
DOI: 10.1021/acssynbio.9b00080
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Flexibility of the Prochlorosin 2.8 Scaffold for Bioengineering Applications

Abstract: Cyclization is a common strategy to confer proteolytic resistance to peptide scaffolds. Thus, cyclic peptides have been the focus of extensive bioengineering efforts. Ribosomally synthesized and posttranslationally-modified peptides (RiPPs) are a superfamily of peptidic natural products that often contain macrocycles. In the RiPP family of lanthipeptides, macrocyclization is accomplished through formation of thioether crosslinks between cysteines and dehydrated serines/threonines. The recent production of lant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 78 publications
0
51
0
3
Order By: Relevance
“…Intriguingly, although their core peptide sequences are highly diverse, there are some hints that they are not random. For instance, engineering studies have shown that the substrate tolerance of ProcM is not limitless and that unlike the natural substrates that have been investigated, which generally make single ring patterns, non-natural substrates in which the positions of Ser/Cys are altered often lead to incomplete cyclization [109]. These observations suggest that despite their diversity, the core peptides in the genomes may have undergone selection to be good substrates for ProcM.…”
Section: How Might Prochlorosin Biosynthetic Pathways Have Evolved?mentioning
confidence: 99%
“…Intriguingly, although their core peptide sequences are highly diverse, there are some hints that they are not random. For instance, engineering studies have shown that the substrate tolerance of ProcM is not limitless and that unlike the natural substrates that have been investigated, which generally make single ring patterns, non-natural substrates in which the positions of Ser/Cys are altered often lead to incomplete cyclization [109]. These observations suggest that despite their diversity, the core peptides in the genomes may have undergone selection to be good substrates for ProcM.…”
Section: How Might Prochlorosin Biosynthetic Pathways Have Evolved?mentioning
confidence: 99%
“…These studies resulted in the discovery of lanthipeptide inhibitors of HIV budding process, 15 urokinase plasminogen activator 16 and α v β 3 integrin binders. 13 Similarly, we anticipate that the integration of the FIT-Laz system with powerful in vitro screening techniques such as mRNA display 66 will provide access to artificial thiopeptides with desirable pharmacological profiles for drug discovery purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Eine dieser Varianten zeigte ebenfalls eine hohe Bindungsaffi nität zu dem αvβ3-Integrin (Abb. 2E, [9]).…”
Section: Das Lanthipeptid Prochlorosin 28unclassified
“…Durch die Nutzung degenerierter Oligonukleotid-Primer konnte eine Bibliothek aus etwa 10 6 verschiedenen Prochlorosin-2.8-Varianten erzeugt werden [10]. Durch Screening dieser Bibliothek konnte ein Inhibitor der Protein-Protein-Interaktion zwischen dem HIV-p6-Protein und der UEV-Domäne des humanen Proteins TSG101 identifi ziert werden [9]. Diese Wechselwirkung ist essenziell für die Knospung von HIV-Partikeln in infi zierten Zellen.…”
Section: Das Lanthipeptid Prochlorosin 28unclassified